구개부에 발생한 다형성 저등급 선암종의 치험례 - 신영민(Young-Min Shin); 최소영(So-Young Cho); 김진욱(Jin-Wook Kim); 변기정(Ki-Jung Byeon); 김진수(Chin-Soo Kim) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2011)
Polymorphous low-grade adenocarcinomas (PLGA) are distinctive salivary gland neoplasms with a propensity to arise from the minor salivary glands. The most frequent location of PLGA is the palate, even though other locations have been described. Previously used terms for PLGA include lobular carcinoma and terminal duct carcinoma. Although the frequency of the tumor is unknown, the recognition of PLGA as an individual tumor has increased with the establishment of specific histopathological criteria characterizing the PLGA. The first choice of treatment is a wide surgical excision including the subjacent bone if necessary. The prognosis is generally good and the recurrence rate ranges from 17% and 22%. Distant metastases is unusual (9%) but occur mainly in the regional lymph nodes. This is a case report of a 67 year old female patient with PLGA who was treated with a wide excision by layers (2 stage) of the lesion including the surrounding bone. We present this case with a review of the relevant literature. KCI Citation Count: 2